CAP102 - Advanced Programming and Data Structure August/September 1998 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1998)
Stamford College Group School Of Computer Sciences (SOCS) Bachelor of Computer Science (Hons) External Degree USM Programme (In Collaboration with Universti Sains Malaysia) August/September 1998 CAP102 - Advanced Programming and Data Structure Time : [3 hours]